2020
DOI: 10.1016/j.copsyc.2019.07.043
|View full text |Cite
|
Sign up to set email alerts
|

The effects of low socioeconomic status on decision-making processes

Abstract: Low income groups are often criticised for making decisions that harm their long-term life outcomes. This article reviews research that attempts to understand these decisionmaking patterns as a product of adaptive responses to the situation of low socioeconomic status. It proposes that low income contexts present socioecological cues concerning resource scarcity, environmental instability, and low subjective social status, which trigger a regulatory shift toward the present and the tuning of cognitive skills a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
70
0
5

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 112 publications
(77 citation statements)
references
References 98 publications
(91 reference statements)
2
70
0
5
Order By: Relevance
“…These results showed that, in the utilization of health services, especially high-level health services, high-SES migrant workers had more advantages. Compared with migrant workers with low SES, migrant workers with high SES had a better living environment and more resources [ 39 , 40 ]. Therefore, considering that medical supplies are classified according to quality level, migrant workers with high SES might be more capable of obtaining better medical services due to their resource advantages.…”
Section: Discussionmentioning
confidence: 99%
“…These results showed that, in the utilization of health services, especially high-level health services, high-SES migrant workers had more advantages. Compared with migrant workers with low SES, migrant workers with high SES had a better living environment and more resources [ 39 , 40 ]. Therefore, considering that medical supplies are classified according to quality level, migrant workers with high SES might be more capable of obtaining better medical services due to their resource advantages.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, although this study identified both state and trait predictors of costly, reactive aggression, it did not examine the effects of longer-term situational or environmental factors. This is important as physical and social environmental influences have been identified as key determinants of self-control and decision-making processes (Sheehy-Skeffington, 2020). This emerging body of research demonstrates that it is not only the short-term situational context that influences self-control, impulsivity, and aggression, but chronic exposure to environmental stressors, structural prejudice against groups, financial and environmental instability, and the effects of low socio-economic status can have major impacts (Sheehy-Skeffington, 2020;Lawson et al 2018;Figueredo et al 2020).…”
Section: Discussionmentioning
confidence: 99%
“…Importantly, there are key environmental influences which lead to lower selfcontrol and similar psychological processes. Research demonstrates that chronic stress, unemployment, resource scarcity, environmental instability, and other stressors can have a significant influence (Lovallo, 2013;Sheehy-Skeffington, 2020). Thus, the relationship between self-control and aggression is likely affected by complex interactions between more stable dispositional differences in self-control and those in the short-and long-term which are heavily shaped by the environment and changing circumstances.…”
mentioning
confidence: 99%
“…Although the homogeneity of the condition presented common challenges, homogeneity of demographics such as socioeconomic status, race, and gender is a limitation of the study. As our participants had a higher education and socioeconomic status than the national average, they might experience lower resource scarcity and higher environmental stability, and thus have more opportunity for focusing on future needs, critical thinking, and self-reflection [ 69 ]. In addition, as participants were recruited from a text-based online support group, they may have fewer symptoms relating to communicative or social ability than other people with brain injury.…”
Section: Discussionmentioning
confidence: 99%